Konsep Self Awareness Dan Perilaku Enterpreneur (Penggunaan Perspektif Perilaku Nabi Muhammad SAW Dan Perspektif Psikologi Serta Enterpreneurship) - Riyanda Utari (LPPAIK Universitas Muhammadiyah Bandung, 2021)
Self-awareness and entrepreneurial behavior are aspects that are interrelated with each other, Entrepreneurship that does not have a reference in will develop behaviors that are detrimental to themselves and others. As a result, the business carried out can be short-lived and suffer losses. Entrepreneurs must realize that there are points that must be established and developed so that self-awareness is not only a reason for doing entrepreneurship activities but also has certain patterns taken from concrete examples of humans who are role models for Muslims, namely the prophet Muhammad SAW. Therefore, it is necessary to discuss self-awareness and entrepreneurial behavior based on descriptive studies using library research data collection and qualitative data analysis taken from deductive discussions.